Turkmenistan : Background Paper and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1995)
This Background Paper and Statistical Appendix for Turkmenistan examines the developments since November 1993, when the manat was introduced as the national currency. Developments in the real sector and systemic reforms are discussed. Fiscal policies, monetary and credit policies, external developments, and the exchange and trade system are described. The paper highlights that over the medium term, the path toward sustainable growth clearly includes the development of alternative routes for the shipment of gas outside the territory of the Former Soviet Union.